Submaximal Exercise Task Post Clinical Balance in COPD Patients and its Correlation with Quadriceps Girth, Body Mass Index and Disease Severity (Indian Journal of Forensic Medicine & Toxicology, 2020)
Purpose: To study and compare the effect of submaximal exercise on static and dynamic balance in patientswith severe and moderate chronic obstructive pulmonary disease (COPD) and correlation of the balanceimpairments with disease severity, quadriceps girth and body mass index (BMI).Methods: A sample of convenience of 45 middle aged participants (mean age 53.47 ± SD 4.775), including15 with severe COPD, 15 with moderate COPD who were not undergoing pulmonary rehabilitation programand 15 healthy controls were included. The subjects performed Timed Up and Go Test (TUG) for dynamicbalance and quiet standing to assess postural sway using sway meter with eyes closed and opened in narrow,semi tandem and tandem stance for 30 seconds. The balance variables were then correlated to forcedexpiratory volume in one second (FEV1), quadriceps girth and body mass index. Significance was set atalpha less than 0.05.Results: when compared to healthy controls, significant differences were found in postural sway in all thestances in severe COPD patients, and in semi tandem and tandem stances in moderate COPD patients. TUGtest significantly differed in both severe and moderate COPD (p=0.0001) and no difference between severeand moderate COPD TUG test was found. Moderate negative correlation was found between FEV1 andpostural away in few stances whereas no correlation was found with quadriceps girth and BMI of COPDpatients.Conclusion: Static as well as dynamic balance are affected in COPD patients with postural sway affectedmore in severe COPD than moderate COPD leading to functional disability and risk of falls which increaseswith increase in age. Balance alterations can be moderately correlated to FEV1.